Una mirada a la creatividad del docente desde una práctica pedagógica reflexiva (2019)
The article aims to analyze the creativity of the teacher in the context of emerging theoretical approaches such as reflective pedagogical practice. Methodologically, two moments of research are approached: firstly, we work with the technique of the review and documentary anal-ysis to reveal the treatment that the authors make of the concept of creativity based on the reflective practice of the teacher. Secondly, work sessions are developed, such as seminars - workshops where discussion groups are formed, with teachers from the area of Philosophy and Letters of the University of Chihuahua, Mexico, who in collective construction approach a collegial concept of creativity; The concept is validated through the observation of the discussion groups in support of the accompaniment in processes of: didactic planning - pedagogical intervention - instructional evaluation. The results highlight teaching competencies, associ-ated with their creativity for didactic mediation from a reflexive position, where strengths and gaps to be resolved are identified. It concludes the need to consoli-date a creative education based on the resignification of pedagogical practice, depending on the teacher’s ways of acting and within the framework of socio-contextual transformations.